An experimental investigation of the elastic stress investigation on crack branching in fiber-reinforced composites - Ng, Chee Yong (2014)
Fiber-reinforced composite has the advantages of being light in weight with superior properties, where it gives the ability to customize the fiber and matrix material to attain the desire properties for usage and application. The common failure is dependent on the fiber diameter and young’s modulus, also the facture being one of the type of failure resulted by matrix crack, fiber fracture and fiber-matrix interface crack. Many research uses fracture mechanics Mode I linear elastic fracture mechanics to study the crack propagation of the fiber-reinforced matrix. It helps to determine the material reliability when crack occurs, giving a value where the crack will propagate known as the stress intensity factor at the crack tip or the fracture toughness of the homogenous linear elastic material. The crack will propagate when the stress factor exceed the stress intensity factor result to the failure of the part. Finite element method is applied to study the crack propagation with reference of the stress intensity factor using the finite element software Abaqus. The stimulation is divide into 3 different setups where for each setup the part is first assume as a homogenous material and the result is used as comparison to the theoretical mathematics calculation using the linear elastic fracture mechanics method. Proper changes of the finite elements software is the key to the accuracy of the stimulation, especially the node of the mesh definite for the various area of the part, for example the crack area. The 3 different parameter of the setups are, first with varying young’s modulus of the fiber, second the varying crack distance to the fiber and last the varying diameter of the fiber. Where it will allow the studies of the effects of the young’s modulus, crack distance and fiber diameter effects on the stress intensity factor. The result of all the stimulation shows a similar pattern, with the use of lower young’s modulus for the fiber compared to the matrix generally improve the stress intensity factor of the part. Hence it shows that using a fiber-reinforced composite it provided a better stress intensity value as compared to a homogenous material in this case. Furthermore, with the decrease of the crack distance the stress intensity factor increased for the fiber, where it further reiterate that using a fiber with lower young’s modulus will aid in the improve in the stress intensity factor. Lastly, with a bigger fiber diameter, similar dimension to the crack length, provided a better stress intensity factor as compare to the fiber with smaller diameter.